Designing an E-Module on the Solar System to Develop Critical Thinking Skills - Vebrianto, Rian; Lilandariati, Fadhillah; Yuliastrin, Adisti; Hardila, Dilva; Sukor, Nur Suhaidah (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
This study aimed to develop learners' critical thinking abilities through concentrated application in related learning activities. A quasi-experimental design of the Pretest-Posttest Non-Equivalent Control Group type was employed. The study was done between January and February 2023 with a sample of 60 junior high school students in grade VII, divided evenly into an experimental group and a control group, each with 30 participants, focused on the solar system. The experimental group utilized problem based learning (PBL) e-modules, while the control group followed conventional teaching methods. The instrument used in this study included a critical thinking variable with four components in the form of a multiple-choice exam with a reliability value of 0.183, allowing it to evaluate students' critical thinking skills. The data were collected during the pretest and after treatments by administering the posttest. After the SPSS analysis, the data was shown descriptively and inferentially. The results revealed a notable difference in critical thinking capabilities between students involved in PBL-based e-modules and those taught using conventional approaches (P < 0.01). Therefore, the study shows that including PBL-based e-modules into the curriculum could improve students' critical thinking ability quite successfully.